2021
DOI: 10.5334/jbsr.2409
|View full text |Cite
|
Sign up to set email alerts
|

Granular Cell Tumor: A Mimicker of Breast Carcinoma

Abstract: Teaching point: Granular cell tumors are rare soft tissue tumors that may occur in the breast. While almost always benign, they may mimic a malignant tumor both clinically and on imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…6,13,21 Its present name, granular cell tumor, is derived from the presence of abundant granular eosinophilic cytoplasm in their cells. 23…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,13,21 Its present name, granular cell tumor, is derived from the presence of abundant granular eosinophilic cytoplasm in their cells. 23…”
Section: Discussionmentioning
confidence: 99%
“…2,31,33 Calcifications are rare. 13,23 On ultrasound, they are hypoechoic or heterogeneous, with margins ranging from circumscribed to not circumscribed. 2,31,33 (Figure 6).…”
Section: Granular Cell Tumor In the Breastmentioning
confidence: 99%
“…Mammography demonstrates spiculations and architectural distortions [93] usually The current literature on these rare tumors has primarily involved surgical excision, and this is generally accepted as the mainstay of management [77] despite the low risk of malignant transformation [85]. Their natural history is not understood well enough for observation to be recommended.…”
Section: Granular Cell Tumorsmentioning
confidence: 99%
“…Mammography demonstrates spiculations and architectural distortions [93] usually without calcifications. Sacranelo et al reported no calcifications in any GCTs reviewed, suggesting that their presence may contradict the diagnosis [94].…”
Section: Granular Cell Tumorsmentioning
confidence: 99%
“…In 8.5% of cases, it is a solitary, palpable, painless mass in the breast. Malignancy has been reported in 0.5% to 2.0% of cases 21 . A granular cell tumor more frequently occurs in the upper outer quadrant.…”
Section: Granular Cell Tumormentioning
confidence: 99%